Coffee and Counsel Clinic: Constructing a More Comfortable Place for Legal Aid in the Sub-Urban Community - Waspiah, Waspiah; Rodiyah, Rodiyah; Setiawan, Andry; Cahyani, Kartika Fajar; Pertiwi, Adinda Ratna; Bimantara, Bayu (The Indonesian Journal of International Clinical Legal Education, 2021)
Legal assistance is one of the needs of the community in the midst of many legal cases today. The existing consultations and assistance also seem formal and very rigid, such as being carried out in offices and the like. In fact, in the success of legal assistance, the comfort of both parties is the main key. This program emphasizes the development of a more comfortable pattern of legal assistance and consultation by combining coffee shops as an alternative place for legal consultation. This program was developed and implemented in Wanureja Village, Tegal, Kendal Regency, Indonesia. This place and program have continually provided clients with access to the best legal advice and representation available, all in an informal, stress-free setting with a low cost for the initial consultation. We meet you where you are most comfortable –an in-person meeting at an attorney’s office, a conversation at the local coffee house, or if you are disabled or incapacitated in any way, at your location.